2018
DOI: 10.21608/ejss.2018.1972.1138
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Their Effect on Some Biological Activities in Abu Suberia Valley- Aswan, Egypt.

Abstract: Data of biological investigation showed that the total counts of bacteria, fungi, yeast, actinomycetes, thermophilic bacteria and cellulolytic bacteria range from 22.4x10 6 to 284x10 6 , 10x10 3 to 27.x10 3 , 6x10 2 to 20x10 2 , 9x10 3 to 19x10 3 , 31x10 3 to 48x10 3 , 0.90x10 4 to 1.82x10 4 CFUg -1 dry soil respectively. The nitrifying and denitrifying bacteria range from 38.0x10 4 to 121.0x10 4 and 30.0x10 2 to 65.0x102 MPN g -1 dry soil, respectively. The biological activities of the concerned enzymes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…8 at a depth of 0-50 cm with an average value of 30.57%. Bahnasawy, (2018) and Ali et al, (2018)found that kaolinite is the dominant mineral compared to other clay minerals. These results showed that the soil under study was not exposed to severe weathering.…”
Section: Mineral Compositions Of Clay Fractionsmentioning
confidence: 99%
“…8 at a depth of 0-50 cm with an average value of 30.57%. Bahnasawy, (2018) and Ali et al, (2018)found that kaolinite is the dominant mineral compared to other clay minerals. These results showed that the soil under study was not exposed to severe weathering.…”
Section: Mineral Compositions Of Clay Fractionsmentioning
confidence: 99%
“…Among the most important of abiotic stresses, drought is particularly detrimental to plant growth and yield in agricultural production, affecting the world's food security (Vurukonda et al, 2016), and if current trends continue, droughtaffected areas are expected to double, and water resources will decrease by 30% by 2050 (Kasim et al, 2013).Therefore, the presence of water in the rhizosphere area is a major parameter that determines the availability of water, oxygen, and nutrients to plants and microorganisms (Van Gestel et al, 1993). Also, the complex interactions among microorganisms, roots, soil, and water in the rhizosphere induce changes in physico-chemical and structural properties of the soil (Haynes andSwift, 1990 andAli et al, 2018). In addition to, the behavior growth of legumes are affected by drought, which can due to reduction in vegetative growth, nodulation, yield and yield component, with a gradual decrease in nutrients of the plants (Costa et al, 2011, Omara and El-Gaafarey, 2018, Abd-Elrahman and Taha, 2018and Abdelhameid, 2019.…”
Section: Introductionmentioning
confidence: 99%